Tshidilo: a step towards understanding spine care in Botswana - Chihambakwe, Mufudzi (Graduate School of Business (GSB), 2025)
This study sought to understand spine care in Botswana by focusing on the experiences of patients in a lower income neighbourhood community clinic in the capital, Gaborone, and the network of health care professionals in the city who manage patients with spinal related disorders. Spinal related disorders (SRDs) are the leading cause of disability worldwide and disproportionately affect people of lower socioeconomic status. It is known that there is low emphasis on the care for SRDs in the training and in practice of health care professionals. Hence the focus of this study was to uncover the structural and societal barriers to the provision of adequate care for SRDs in underserved communities in Botswana The sample included 39 interlocutors made up of patients, health care professionals (HCPs), health administrators and a linguist. Twenty-five of the interlocutors were part of five focus groups of five participants each (3 focus groups of patients only, two focus groups of health care professionals only). Of these focus groups there were three follow-up interviews. Thereafter there were 14 standalone semi-structured interviews. Thematic analysis was employed to mine the data using NVIVO software. The interlocutors highlighted how the health care system in Botswana is more primed to address life threatening, high risk infectious diseases than it is to address non-lethal lifestyle related conditions such as SRDs, despite their ubiquity. Furthermore, health care professionals felt that a policy on musculoskeletal health that encompasses SRDs would lead to clinical guidelines and resources to empower health care professionals to provide adequate care for SRDs. Tshidilo, understood as ‘massage', has been a practice in Botswana for the management of SRDs and this has implications for the way modern spine care is given and received for SRDs in Botswana. The word tshidilo has many more applications and can be used as a principle and approach for how to better understand and manage SRDs in Botswana and beyond. Future research can explore tshidilo and other indigenous health care approaches as an indigenous knowledge study to complement modern health care approaches to health care conditions.